Emerging technologies and international security machines, the state and war - Steff, Reuben; Soare, Simona; Burton, Joe, 1977- (London : Routledge, 2020)
This book offers a multidisciplinary analysis of emerging technologies and their impact on the new international security environment across three levels of analysis. While recent technological developments, such as Artificial Intelligence (AI), robotics and automation, have the potential to transform international relations in positive ways, they also pose challenges to peace and security and raise new ethical, legal and political questions about the use of power and the role of humans in war and conflict. This book makes a contribution to these debates by considering emerging technologies across three levels of analysis: (1) the international system (systemic level) including the balance of power; (2) the state and its role in international affairs and how these technologies are redefining and challenging the state's traditional roles; and (3) the relationship between the state and society, including how these technologies affect individuals and non-state actors. This provides specific insights at each of these levels and generates a better understanding of the connections between the international and the local when it comes to technological advance across time and space The chapters examine the implications of these technologies for the balance of power, examining the strategies of the US, Russia, and China to harness AI, robotics and automation (and how their militaries and private corporations are responding); how smaller and less powerful states and non-state actors are adjusting; the political, ethical and legal implications of AI and automation; what these technologies mean for how war and power is understood and utilized in the 21st century; and how these technologies diffuse power away from the state to society, individuals and non-state actors. This volume will be of much interest to students of international security, science and technology studies, law, philosophy, and international relations.
OCLC-licensed vendor bibliographic record.
Keywords: Technology and state -- History -- 20th century; Military art and science -- History -- 21st century; International relations; Technological innovations -- Political aspects; National security; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Political Freedom & Security / General